2002
DOI: 10.1007/s12043-002-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

A new ultrasonic method to detect chemical additives in branded milk

Abstract: A new ultrasonic method -thermoacoustic analysis -is reported for the detection of the added chemical preservatives in branded milk. The nature of variation and shift in the thermal response of the acoustic parameters specific acoustic impedance, adiabatic compressibility and Rao's specific sound velocity for different samples of branded milk as compared to the chemical added pure milk are explained as due to the presence of chemicals in these branded samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…It is known that long continuous intake of sodium carbonate or bicarbonate and formalin might be harmful, as it causes damage to the gastrointestinal tract, primarily the stomach and lower oesophagus (Resmini et al, 1988). In addition, it may have a carcinogenic effect on human (Haddad and Winchester, 1990) and severe acidosis which result from rapid conversion of formaldehyde to formic acid (Mohanan et al, 2002). Table 2 reveals that the mean value of tetracycline residues in the examined samples of UHT milk was 23.62 ± 7.01 with a minimum value of 10.00 and a maximum value of 78.71 ppb.…”
Section: Resultsmentioning
confidence: 98%
“…It is known that long continuous intake of sodium carbonate or bicarbonate and formalin might be harmful, as it causes damage to the gastrointestinal tract, primarily the stomach and lower oesophagus (Resmini et al, 1988). In addition, it may have a carcinogenic effect on human (Haddad and Winchester, 1990) and severe acidosis which result from rapid conversion of formaldehyde to formic acid (Mohanan et al, 2002). Table 2 reveals that the mean value of tetracycline residues in the examined samples of UHT milk was 23.62 ± 7.01 with a minimum value of 10.00 and a maximum value of 78.71 ppb.…”
Section: Resultsmentioning
confidence: 98%
“…In this method, the density and ultrasonic velocity are determined for different samples while the temperature is kept fixed for a particular measurement. Ultrasonic velocities were measured by a single crystal ultrasonic interferometer at a frequency of 2 MHz [5] Piezoelectric Sensor-Jiali et al have reported the determination of bacteria counts in fresh milk in real-time using piezoelectric transducer. The detection system consists of a cell for detection, oscillator, frequency counter and computer in which self-developed software is installed to capture the transducer response with the change of culture media during bacteria growth.…”
Section: Conductancementioning
confidence: 99%
“…So to increase the shelf life, addition of chemical preservatives in branded milk [21] is a very common practice. Sometimes hydrogen peroxide (H 2 O 2 ) is used as a preservative [22].…”
Section: Hydrogen Peroxide (H 2 O 2 )mentioning
confidence: 99%